Willingness‑to‑Pay for Energy Efficiency: Evidence from the European Common Market - Kesselring, Anne Maria (Environmental & Resource Economics, 2023)
This paper explores the willingness-to-pay for energy efficiency by exploiting variation across products and countries within the EU market for household appliances. Based on scanner data at product-level, I use the hedonic method to estimate implicit prices for energy efficiency and derive implicit discount rates. The paper argues that the implicit price will be underestimated when energy consumption is not only a determinant of operating cost but also is positively associated with other features of a product. The empirical analysis confirms that estimates of the willingness-to-pay are higher when this effect is accounted for in the estimation. This is especially true of product types for which the heterogeneity of usage intensity is low. The results thus indicate that the energy efficiency gap is smaller than found in earlier studies.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Energy efficiency; Energy efficiency gap; Hedonic prices; Household appliances; Implicit discount rate; White goods